Selective harmonics elimination technique in single phase unipolar H -bridge inverter - Aboadla, Ezzidin Hassan Elmabrouk A; Khan, Sheroz; Habaebi, Mohamed Hadi; Gunawan, Teddy Surya; Hamida, Belal Ahmed; Tohtayong, Majdee (IEEE, 2017)
Specific odd harmonics can be mitigated by operating the semiconductor switches in H-bridge inverters at optimized switching angles of the PWM signals. These switching angles can be achieved by deriving a set of nonlinear equations using Selective Harmonic Elimination Pulse Width Modulation (SHE-PWM) technique. Modulation index (ma) is a significant parameter used to control the amplitude of the fundamental output voltage of DC-AC inverter. By changing the value of modulation index the Total Harmonics Distortion (THD) also will change. In this paper, the performance of single phase H-bridge inverter using SHE-PWM scheme with varying the modulation index is evaluated. In order to achieve a minimum THD, a different number of nonlinear equations are used to calculate the switching angles. The performance of a single phase H-bridge inverter is simulated in Matlab-Simulink.